Refraction point estimation-based backprojection for autofocusing technique in unknown layered scenes using ground penetrating radar data - Xu, Zihan; Su, Fulin; Xu, Guodong (Journal of applied remote sensing, 2022)
Backprojection (BP) algorithm is successfully used to focus the layered scenes using ground-penetrating radar data. However, the BP algorithm with the time-consuming refraction point computation is impractical to autofocus in the layered scenes lacking medium information, where iterative focusing for estimating information continuously accumulates the calculation time of refraction points. Therefore, we propose a refraction point estimation (RPE)-based BP algorithm for autofocusing technique in unknown layered scenes. Our RPE algorithm, including two steps, directly expresses the refraction point. The first step coarsely estimates an initial position using an adjustment factor. Subsequently, the second step precisely converts the quartic equation of the refraction point into a linear form subject to the coarse estimation. Following this, we propose an RPE-based BP autofocusing technique to efficiently complete information estimation and refocusing. Compared with the existing algorithms, the proposed RPE algorithm directly estimates the refraction point and avoids iteration. The results indicate that the RPE-based BP algorithm has significant advantages in efficiency and accuracy, prompting the practical application of the BP autofocusing in unknown layered scenes.